Environment-friendly low-smoke halogen-free flame-retardant twisted-pair cable and preparation method thereof
Patent Information
- Application Number
- CN202611124935.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-13
AI Technical Summary
[0006]针对现有双绞型电缆在低烟无卤阻燃体系中易出现阻燃与力学性能难以兼顾、燃烧过程中烟释放较大、火焰易沿双绞结构蔓延、绝缘层与导体界面结合稳定性不足以及整线耐火完整性较弱等问题,本申请提供了一种环保型的低烟无卤阻燃型双绞型电缆及其制备方法
1、本申请通过在双绞导体单元外周依次设置绝缘层、阻燃隔离层和外护套层,使电缆形成由内至外功能分工明确的多层协同结构。其中,绝缘层和外护套层均采用低烟无卤阻燃复合材料,双绞导体单元外周进一步设置阻燃隔离层,从而使材料本体阻燃与结构阻隔作用相互配合。低烟无卤阻燃复合材料中的金属氢氧化物阻燃剂在受热过程中吸收热量并释放不燃组分,硼酸锌对烟释放和残炭稳定具有促进作用,鞣酸金属配位材料则有利于在燃烧过程中形成连续而致密的炭化层。因此,与未引入鞣酸金属配位材料或未设置专用阻燃隔离层的结构相比,本申请在提高氧指数、降低烟密度、抑制热释放以及减缓火焰沿线蔓延方面表现出更好的综合效果。
Smart Images

Figure CN122907417A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the technical field of preparation of environmentally friendly low-smoke halogen-free flame-retardant cables, and discloses an environmentally friendly low-smoke halogen-free flame-retardant twisted pair cable and its preparation method. Background Technology
[0002] Twisted-pair cables, due to their compact structure, stable transmission, and convenient installation, are widely used in communication connections, control transmissions, and equipment wiring. In densely populated buildings, rail transit, medical equipment, and intelligent manufacturing systems, cables not only need to possess basic conductivity and insulation functions during operation, but also need to meet higher requirements for flame retardancy, low smoke, and environmental protection. Especially in the event of a fire, if the cable material releases a large amount of smoke and heat, it can easily affect personnel evacuation and the continuous operation of equipment. Therefore, improving twisted-pair cables using low-smoke halogen-free flame-retardant systems has become an important development direction for this type of product.
[0003] Chinese patent application CN121237501A discloses a halogen-free, low-smoke, flame-retardant polyolefin cable. It employs a multi-layered sheath and wrapping structure, featuring a ceramicized polyolefin outer sheath combined with an inner sheath, flame-retardant wrapping tape, a water-blocking layer, and a metal sheath layer to improve the cable's heat insulation, fire resistance, and continuous power supply capabilities under high-temperature combustion conditions. Its core improvement focuses on maintaining the overall shape and protective capability of the cable in a fire through the ceramicization of the outer sheath and the multi-layered wrapping structure. Therefore, existing technologies for halogen-free, low-smoke, flame-retardant cables primarily address the problems of sheath softening, structural collapse, and insufficient continuous power supply under high-temperature flames. Their technological focus is more on the ceramicization of the outer sheath material, the fire resistance of the wrapping layer, and the increase in the overall protection level.
[0004] However, in existing technologies, the high-filler flame-retardant systems used in the preparation of materials can easily reduce the toughness of the materials and worsen their processing fluidity, thereby affecting the extrusion coating quality and the overall stability of the production line. In addition, the interfacial bonding state between the conductor and the insulation layer also affects the structural integrity of the cable under bending, thermal aging, and fire conditions. If the interfacial bonding is insufficient, local debonding and unstable coating can easily occur, thus reducing the reliability of the entire production line.
[0005] Therefore, how to balance the flame retardant and smoke-suppressing properties of the material itself, the flame blocking capability under the twisted pair structure, the interfacial bonding stability between the conductor and the insulation layer, and the forming reliability in the industrial processing of cables in a low-smoke halogen-free flame retardant system remains a technical problem that needs to be further solved in this field. Summary of the Invention
[0006] To address the problems of existing twisted-pair cables in low-smoke halogen-free flame-retardant systems, such as difficulty in balancing flame retardancy and mechanical properties, excessive smoke release during combustion, easy flame spread along the twisted-pair structure, insufficient stability of the interface between the insulation layer and the conductor, and weak overall fire resistance integrity, this application provides an environmentally friendly low-smoke halogen-free flame-retardant twisted-pair cable and its preparation method. This technical solution constructs a layered structure consisting of twisted-pair conductor units, an insulation layer, a flame-retardant isolation layer, and an outer sheath layer. Combined with a low-smoke halogen-free flame-retardant composite material containing tannic acid metal coordination materials, a conductor surface coupling modification layer, and a corresponding step-by-step preparation process, the flame-retardant and smoke-suppressing effects of the material itself, the thermal insulation barrier effects between structural layers, and the interface stabilization effects between the conductor and the insulation layer work together to improve the cable's flame retardant performance, reduce smoke density, suppress flame spread along the cable, and improve the overall mechanical reliability and fire resistance integrity.
[0007] The present invention provides the following technical solution: an environmentally friendly low-smoke halogen-free flame-retardant twisted-pair cable, comprising a twisted-pair conductor unit, an insulation layer, a flame-retardant isolation layer and an outer sheath layer arranged radially from the inside to the outside; The twisted pair conductor unit consists of two insulated wire cores twisted together, each insulated wire core including a conductor and an insulating layer covering the outside of the conductor; Both the insulation layer and the outer sheath layer are made of low-smoke halogen-free flame-retardant composite material; The flame-retardant isolation layer is disposed on the outer periphery of the twisted pair conductor unit; The pitch of the twisted pair conductor unit is 20 mm to 120 mm; The conductor is an annealed copper conductor, and a coupling modification layer is provided on the outer surface of the annealed copper conductor. The coupling modification layer is a silicon-containing interface layer formed after surface cleaning, acetic acid activation, silane hydrolysis treatment and drying curing.
[0008] Further, the low-smoke halogen-free flame-retardant composite material comprises, by weight: 40 to 65 parts of crystalline polyolefin matrix resin, 10 to 28 parts of ethylene-based flexible toughening copolymer, 90 to 170 parts of metal hydroxide flame retardant, 3 to 15 parts of zinc borate as a smoke suppressant, 2 to 12 parts of tannic acid metal coordination material, 1 to 8 parts of dispersion regulator, and 0.2 to 1.5 parts of antioxidant; The tannic acid metal coordination material is a solid powder material formed by the coordination of tannic acid with iron ions, aluminum ions or zinc ions; the metal hydroxide is aluminum hydroxide and / or magnesium hydroxide.
[0009] Furthermore, the crystalline polyolefin matrix resin is a thermoplastic polyolefin resin having ethylene segments and providing the main crystalline phase, selected from one or more of high-density polyethylene, low-density polyethylene, linear low-density polyethylene, ethylene-butene copolymer or ethylene-hexene copolymer; The ethylene-based flexible toughening copolymer is selected from one or more of ethylene octene copolymer, ethylene vinyl acetate copolymer, ethylene ethyl acrylate copolymer, ethylene butyl acrylate copolymer, or ethylene methacrylate copolymer.
[0010] Furthermore, the antioxidant is a stabilizer used to inhibit the thermo-oxidative degradation of the low-smoke halogen-free flame-retardant composite material during melt blending, extrusion molding, and thermal aging, and is selected from one or more of tetrakis[β-3,5-di-tert-butyl-4-hydroxyphenylpropionate] pentaerythritol ester, dilauryl thiodipropionate, trinonylphenyl phosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl) phosphite, or distearate thiodipropionate.
[0011] Furthermore, the dispersion regulator is selected from one or more of stearic acid, lauric acid, palmitic acid, behenic acid, or oleic acid.
[0012] Furthermore, the preparation method of the low-smoke halogen-free flame-retardant composite material includes the following steps: 1) Tannic acid is added to deionized water to prepare a tannic acid solution with a mass fraction of 2% to 12%, and then a metal salt solution containing iron salt, aluminum salt or zinc salt is added to carry out a coordination reaction. The mass ratio of metal ions to tannic acid in the metal salt solution is (1:3) to (1:12), the reaction temperature is 20℃ to 60℃, and the reaction time is 10 min to 120 min to obtain a tannic acid metal coordination slurry. 2) After solid-liquid separation, washing and drying, the tannic acid metal coordination slurry is used to obtain tannic acid metal coordination material powder, wherein the drying temperature is 50℃~90℃ and the drying time is 2 h~12 h. 3) By weight, the crystalline polyolefin matrix resin, ethylene-based flexible toughening copolymer, metal hydroxide flame retardant, zinc borate, the tannic acid metal coordination material, dispersant and antioxidant are added to a high-speed mixer for premixing. The premixing temperature is 60℃~110℃ and the premixing time is 3 min~15 min. 4) The premixed material is fed into a twin-screw extruder for melt blending and extrusion granulation. The melt blending temperature is 120℃~190℃ and the screw speed is 120 rpm~450 rpm to obtain the low-smoke halogen-free flame-retardant composite material.
[0013] Furthermore, the flame-retardant insulating layer is a wrapped mica composite tape.
[0014] This application also provides a method for preparing the environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable as described above, comprising the following steps: S1: Low-smoke halogen-free flame-retardant composite materials for insulation layers and outer sheath layers are prepared according to the preparation method of the low-smoke halogen-free flame-retardant composite material. S2: The low-smoke halogen-free flame-retardant composite material for the insulation layer is added to a mixer and mixed at a temperature of 120℃~165℃ for 5 min~20 min. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at a temperature of 130℃~185℃ and a screw speed of 150 rpm~400 rpm to obtain the insulation layer material. The low-smoke halogen-free flame-retardant composite material for the outer sheath layer is added to a mixer and mixed at a temperature of 125℃~170℃ for 6 min~25 min. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at a temperature of 135℃~190℃ and a screw speed of 150 rpm~420 rpm to obtain the outer sheath layer material. S3: After surface cleaning and coupling modification of the annealed copper conductor, the insulating material is wrapped around the outside of the annealed copper conductor using an extrusion device to obtain two insulated wire cores. S4: Twist the two insulated wire cores at a set pitch and wrap the flame-retardant insulation layer around their outer periphery to obtain a twisted conductor unit with a flame-retardant insulation layer. S5: The outer sheath material is extruded onto the outside of the flame-retardant isolation layer using an extrusion device. The extrusion temperature is 140℃~195℃, the extrusion pressure is 8 MPa~25 MPa, and the traction speed is 10 m / min~80 m / min. After extrusion, the cable is cooled, shaped, and wound up to obtain the environmentally friendly, low-smoke, halogen-free, flame-retardant twisted pair cable.
[0015] Furthermore, in step S2, the mixing temperature during the preparation of the insulating layer material is 5°C to 20°C lower than the mixing temperature during the preparation of the outer sheath material, and in step S5, the extrusion temperature of the outer sheath material is 5°C to 15°C higher than the covering temperature of the insulating layer material, so that the insulating layer preferentially maintains a flexible covering state and the outer sheath layer preferentially forms a dense covering layer.
[0016] Furthermore, the surface cleaning and coupling modification treatment of the conductor in step S3 includes: S31: First, place the annealed copper conductor in a cleaning solution for surface cleaning. The cleaning solution, based on the total mass of the cleaning solution, includes 60% to 85% ethanol, 5% to 20% isopropanol and the remainder deionized water. The cleaning temperature is 20°C to 45°C and the cleaning time is 1 min to 8 min. S32: The cleaned annealed copper conductor is then placed in an activation solution for surface activation. The activation solution, based on the total mass of the activation solution, includes 0.2% to 2.5% acetic acid and the remainder deionized water. The activation temperature is 20℃ to 40℃ and the activation time is 10 s to 90 s. S33: Subsequently, the activated annealed copper conductor is immersed in a coupling treatment solution, wherein the coupling treatment solution, based on the total mass of the coupling treatment solution, includes 0.5%–4% silane coupling agent, 50%–80% ethanol, 5%–20% isopropanol, 0.1%–1.2% acetic acid, and the balance deionized water, and the immersion time is 10 s–180 s; after immersion, it is dried at 60℃–130℃ for 1 min–15 min, and cured at 80℃–150℃ for 30 s–10 min to form a coupling modification layer on the surface of the annealed copper conductor.
[0017] The technical solution of this application has the following beneficial effects: 1. This application achieves a multi-layered, collaborative cable structure with clearly defined functions from the inside out by sequentially setting an insulation layer, a flame-retardant isolation layer, and an outer sheath layer around the outer periphery of the twisted-pair conductor unit. Both the insulation layer and the outer sheath layer utilize low-smoke halogen-free flame-retardant composite materials, and a further flame-retardant isolation layer is set around the outer periphery of the twisted-pair conductor unit, thus combining the flame-retardant properties of the material itself with the structural barrier effect. The metal hydroxide flame retardant in the low-smoke halogen-free flame-retardant composite material absorbs heat and releases non-combustible components during heating; zinc borate promotes smoke release and char stability; and tannic acid metal coordination materials facilitate the formation of a continuous and dense char layer during combustion. Therefore, compared to structures without tannic acid metal coordination materials or without a dedicated flame-retardant isolation layer, this application exhibits better overall performance in increasing the oxygen index, reducing smoke density, suppressing heat release, and slowing the spread of flames along the line.
[0018] 2. This application simultaneously introduces a crystalline polyolefin matrix resin, an ethylene-based flexible toughening copolymer, a dispersant, and an antioxidant into a low-smoke halogen-free flame-retardant composite material. This allows the highly filled flame-retardant system to maintain good processing stability and mechanical support while retaining its flame-retardant and smoke-suppressing capabilities. The crystalline polyolefin matrix resin provides the main framework of the material, the ethylene-based flexible toughening copolymer improves the toughness and deformation adaptability under high-filling conditions, the dispersant improves the distribution of inorganic fillers and tannic acid metal coordination materials in the resin phase, and the antioxidant reduces the risk of thermo-oxidative degradation during melt blending and extrusion processing. Therefore, the insulation layer and outer sheath not only possess good flame-retardant and smoke-suppressing properties but also maintain relatively stable mechanical properties under thermal aging, bending, and long-term use conditions, thus balancing flame-retardant requirements with practical reliability.
[0019] 3. This application incorporates a silicon-containing interface layer formed on the outer surface of the annealed copper conductor after surface cleaning, acetic acid activation, silane hydrolysis treatment, and drying and curing. This creates a more stable interfacial bond between the conductor and the insulation layer. This silicon-containing interface layer helps reduce interfacial voids and debonding tendency between the conductor and the insulation layer, ensuring better insulation integrity during subsequent twisting, wrapping, and outer sheath extrusion processes. Simultaneously, in step S2, the insulation material and the outer sheath material are respectively subjected to intensive mixing and extrusion granulation. Temperature difference control ensures that the insulation layer preferentially maintains a flexible coating state, while the outer sheath layer preferentially forms a dense coating layer. This guarantees good molding stability and structural consistency of the twisted-pair cable under industrial conditions. Through the synergistic combination of the above material system, interface construction, and layered molding process, this application achieves a coordinated improvement in flame retardancy, smoke suppression, fire resistance integrity, interfacial bonding stability, and processing feasibility within the same cable structure, demonstrating high comprehensive application value. Attached Figure Description
[0020] The invention will now be described in more detail with reference to embodiments and the accompanying drawings. Figure 1 This is a structural cross-sectional schematic diagram of the environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable provided in Embodiment 1 of this application. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1 Combination Figure 1As shown, the environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable provided in this embodiment, arranged radially from the inside out, includes a conductor 1, a coupling modification layer 2 disposed on the outer surface of the conductor 1, an insulation layer 3 covering the outside of the coupling modification layer 2, a flame-retardant isolation layer 4 disposed on the outer periphery of the twisted-pair conductor unit, and an outer sheath layer 5 covering the outside of the flame-retardant isolation layer 4. Two insulated cores covered by the insulation layer 3 are twisted together to form a twisted-pair conductor unit. The internal conductive part of the twisted-pair conductor unit uses annealed copper conductors. The outer surface of the annealed copper conductor is treated with surface cleaning, acetic acid activation, silane treatment, and drying curing to form the coupling modification layer 2, thereby improving the interface bonding between the conductor 1 and the insulation layer 3. Both the insulation layer 3 and the outer sheath layer 5 are made of low-smoke, halogen-free, flame-retardant composite materials, enabling the cable to meet basic insulation protection and external protection requirements while possessing good flame-retardant and smoke-suppressing properties. The flame-retardant insulating layer 4 is located between the twisted-pair conductor unit and the outer sheath layer 5. Under fire conditions, it can delay the inward transfer of heat and inhibit the spread of flames along the twisted-pair structure, thus forming a synergistic barrier effect with the insulation layer 3 and the outer sheath layer 5, ensuring the overall structural integrity of the cable and the continuity of the line under fire conditions. The flame-retardant insulating layer 4 is a wrapped mica composite tape; the pitch of the twisted-pair conductor unit is 20 mm.
[0023] In this embodiment, the low-smoke halogen-free flame-retardant composite materials used for the insulation layer and the outer sheath layer are prepared separately, but both use the same formulation. By weight, the low-smoke halogen-free flame-retardant composite material comprises: 30 parts high-density polyethylene, 22 parts linear low-density polyethylene, 18 parts ethylene-vinyl acetate copolymer, 10 parts ethylene-octene copolymer, 130 parts magnesium hydroxide, 3 parts zinc borate, 12 parts iron tannate coordination material, 4 parts stearic acid, 0.12 parts pentaerythritol tetrakis[β-3,5-di-tert-butyl-4-hydroxyphenylpropionic acid], and 0.08 parts dilauryl thiodipropionate.
[0024] The tannic acid iron coordination material and the low-smoke halogen-free flame-retardant composite material are prepared according to the following steps.
[0025] 1) Add tannic acid to deionized water to prepare a tannic acid solution with a mass fraction of 7%; then add ferric chloride aqueous solution to the tannic acid solution to carry out a coordination reaction, wherein the mass ratio of iron ions to tannic acid is 1:12, the coordination reaction temperature is 20℃, and the coordination reaction time is 60 min, to obtain ferric tannate coordination slurry.
[0026] 2) The iron tannate coordination slurry was subjected to solid-liquid separation, washed with deionized water, and dried at 90°C for 2 hours to obtain iron tannate coordination material powder.
[0027] 3) Based on the above weight proportions, high-density polyethylene, linear low-density polyethylene, ethylene vinyl acetate copolymer, ethylene octene copolymer, magnesium hydroxide, zinc borate, the tannic acid iron coordination material, stearic acid, pentaerythritol tetrakis[β-3,5-di-tert-butyl-4-hydroxyphenylpropionic acid] and dilauryl thiodipropionate are added to a high-speed mixer and premixed at 85°C for 15 min.
[0028] 4) The premixed material is fed into a twin-screw extruder for melt blending and extrusion granulation. The melt blending temperature is 120℃ and the screw speed is 285 rpm. Low-smoke halogen-free flame-retardant composite material for insulation layer and low-smoke halogen-free flame-retardant composite material for outer sheath layer are obtained respectively.
[0029] When preparing cables, follow these steps.
[0030] S1: Prepare low-smoke halogen-free flame-retardant composite materials for insulation layers and outer sheaths according to the methods described in 1) to 4) above.
[0031] S2: The low-smoke halogen-free flame-retardant composite material for the insulation layer is added to a mixer and mixed at 145°C for 5 min. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at 185°C and a screw speed of 150 rpm to obtain the insulation layer material. The low-smoke halogen-free flame-retardant composite material for the outer sheath layer is added to a mixer and mixed at 165°C for 15 min. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at 162°C and a screw speed of 420 rpm to obtain the outer sheath layer material. In this embodiment, the mixing temperature of the outer sheath layer material is 20°C higher than that of the insulation layer material.
[0032] S3: After surface cleaning and coupling modification treatment of the annealed copper conductor, the insulating material is coated on the outside of the annealed copper conductor using an extrusion device to obtain two insulated wire cores; wherein, the coating temperature of the insulating material is 135℃.
[0033] The surface cleaning and coupling modification treatment includes: S31: First, place the annealed copper conductor in a cleaning solution for surface cleaning. The cleaning solution, based on the total mass of the cleaning solution, includes 60% ethanol, 20% isopropanol, and 20% deionized water. The cleaning temperature is 32°C, and the cleaning time is 8 min.
[0034] S32: The cleaned annealed copper conductor is then placed in an activation solution for surface activation. The activation solution, based on its total mass, includes 0.2% acetic acid and 99.8% deionized water. The activation temperature is 40°C and the activation time is 45 seconds.
[0035] S33: Subsequently, the activated annealed copper conductor is immersed in a coupling treatment solution, which, based on the total mass of the coupling treatment solution, comprises 4.0% γ-aminopropyltriethoxysilane, 50% ethanol, 12% isopropanol, 1.2% acetic acid, and 32.8% deionized water; the immersion time is 10 s; after immersion, it is dried at 95°C for 15 min and cured at 80°C for 300 s to form a coupling modification layer on the surface of the annealed copper conductor.
[0036] S4: Twist the two insulated wire cores at a pitch of 20 mm, and wrap the mica composite tape around their outer periphery to obtain a twisted conductor unit with a flame-retardant insulation layer.
[0037] S5: The outer sheath material is extruded onto the outside of the flame-retardant insulation layer using an extrusion device. The extrusion temperature is 140℃, the extrusion pressure is 16 MPa, and the traction speed is 80 m / min. After extrusion, the material is cooled, shaped, and wound up to obtain the environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable. In this embodiment, the extrusion temperature of the outer sheath material is 5℃ higher than the insulation layer material's covering temperature.
[0038] Example 2 This embodiment provides an environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable. The overall structure of the twisted-pair cable is the same as that of Embodiment 1, except for the raw material system and various process parameters. The flame-retardant insulation layer is still a wrapped mica composite tape; the pitch of the twisted-pair conductor unit is 70 mm.
[0039] In this embodiment, the low-smoke halogen-free flame-retardant composite materials used for the insulation layer and the outer sheath layer are prepared separately, but both use the same formulation. By weight, the low-smoke halogen-free flame-retardant composite material comprises: 35 parts low-density polyethylene, 30 parts ethylene-hexene copolymer, 6 parts ethylene-ethyl acrylate copolymer, 4 parts ethylene-octene copolymer, 50 parts aluminum hydroxide, 40 parts magnesium hydroxide, 15 parts zinc borate, 7 parts aluminum tannate coordination material, 1 part lauric acid, 0.8 parts trinonylphenyl phosphite, and 0.7 parts distearate thiodipropionate.
[0040] The aluminum tannate coordination material and the low-smoke halogen-free flame-retardant composite material are prepared according to the following steps.
[0041] 1) Add tannic acid to deionized water to prepare a tannic acid solution with a mass fraction of 2%; then add aluminum sulfate aqueous solution to the tannic acid solution to carry out a coordination reaction, wherein the mass ratio of aluminum ions to tannic acid is 1:7, the coordination reaction temperature is 60℃, and the coordination reaction time is 10 min, to obtain aluminum tannate coordination slurry.
[0042] 2) The aluminum tannate coordination slurry was subjected to solid-liquid separation, washed with deionized water, and dried at 70°C for 12 hours to obtain aluminum tannate coordination material powder.
[0043] 3) Based on the above weight proportions, add low-density polyethylene, ethylene-hexene copolymer, ethylene-ethyl acrylate copolymer, ethylene-octene copolymer, aluminum hydroxide, magnesium hydroxide, zinc borate, the aluminum tannate coordination material, lauric acid, trinonylphenyl phosphite and distearate dipropionate to a high-speed mixer and premix at 60°C for 9 min.
[0044] 4) The premixed material is fed into a twin-screw extruder for melt blending and extrusion granulation. The melt blending temperature is 190℃ and the screw speed is 120 rpm. Low-smoke halogen-free flame-retardant composite material for insulation layer and low-smoke halogen-free flame-retardant composite material for outer sheath layer are obtained respectively.
[0045] When preparing cables, follow these steps.
[0046] S1: Prepare low-smoke halogen-free flame-retardant composite materials for insulation layers and outer sheaths according to the methods described in 1) to 4) above.
[0047] S2: The low-smoke halogen-free flame-retardant composite material for the insulation layer is added to a mixer and mixed at 120°C for 20 minutes. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at 158°C and a screw speed of 400 rpm to obtain the insulation layer material. The low-smoke halogen-free flame-retardant composite material for the outer sheath layer is added to a mixer and mixed at 130°C for 6 minutes. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at 135°C and a screw speed of 285 rpm to obtain the outer sheath layer material. In this embodiment, the mixing temperature of the outer sheath layer material is 10°C higher than that of the insulation layer material.
[0048] S3: After surface cleaning and coupling modification treatment of the annealed copper conductor, the insulating material is coated on the outside of the annealed copper conductor using an extrusion device to obtain two insulated wire cores; wherein, the coating temperature of the insulating material is 180℃.
[0049] The surface cleaning and coupling modification treatment includes: S31: First, place the annealed copper conductor in a cleaning solution for surface cleaning. The cleaning solution, based on the total mass of the cleaning solution, includes 72% ethanol, 5% isopropanol, and 23% deionized water. The cleaning temperature is 20°C, and the cleaning time is 4 min.
[0050] S32: The cleaned annealed copper conductor is then placed in an activation solution for surface activation. The activation solution, based on the total mass of the activation solution, includes 2.5% acetic acid and 97.5% deionized water. The activation temperature is 30°C and the activation time is 10 s.
[0051] S33: Subsequently, the activated annealed copper conductor is immersed in a coupling treatment solution, which, based on the total mass of the coupling treatment solution, comprises 2.0% γ-glycidyl etheroxypropyltrimethoxysilane, 80% ethanol, 5% isopropanol, 0.6% acetic acid, and 12.4% deionized water; the immersion time is 180 s; after immersion, it is dried at 60°C for 8 min and cured at 150°C for 30 s to form a coupling modification layer on the surface of the annealed copper conductor.
[0052] S4: Twist the two insulated wire cores at a pitch of 70 mm, and wrap the mica composite tape around their outer periphery to obtain a twisted conductor unit with a flame-retardant insulation layer.
[0053] S5: The outer sheath material is extruded onto the outside of the flame-retardant isolation layer using an extrusion device. The extrusion temperature is 195℃, the extrusion pressure is 8 MPa, and the traction speed is 45 m / min. After extrusion, the material is cooled, shaped, and wound up to obtain the environmentally friendly, low-smoke, halogen-free, flame-retardant twisted pair cable.
[0054] In this embodiment, the extrusion temperature of the outer sheath material is 15°C higher than the covering temperature of the insulation material.
[0055] Example 3 This embodiment provides an environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable. The overall structure of the twisted-pair cable is the same as that of Embodiment 1, except for the raw material system and various process parameters. The flame-retardant insulation layer is still a wrapped mica composite tape; the pitch of the twisted-pair conductor unit is 120 mm.
[0056] In this embodiment, the low-smoke halogen-free flame-retardant composite materials used for the insulation layer and the outer sheath layer are prepared separately, but both use the same formulation. By weight, the low-smoke halogen-free flame-retardant composite material comprises: 22 parts linear low-density polyethylene, 18 parts ethylene-butene copolymer, 10 parts ethylene-butyl acrylate copolymer, 9 parts ethylene-methacrylate copolymer, 170 parts magnesium hydroxide, 9 parts zinc borate, 2 parts zinc tannate coordination material, 4 parts behenic acid, 4 parts oleic acid, 0.4 parts bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, and 0.4 parts tris(2,4-di-tert-butylphenyl) phosphite.
[0057] The zinc tannate coordination material and the low-smoke halogen-free flame-retardant composite material are prepared according to the following steps.
[0058] 1) Add tannic acid to deionized water to prepare a tannic acid solution with a mass fraction of 12%; then add zinc acetate aqueous solution to the tannic acid solution to carry out a coordination reaction, wherein the mass ratio of zinc ions to tannic acid is 1:3, the coordination reaction temperature is 40℃, and the coordination reaction time is 120 min, to obtain zinc tannate coordination slurry.
[0059] 2) The zinc tannate coordination slurry was subjected to solid-liquid separation, washed with deionized water, and dried at 50°C for 7 hours to obtain zinc tannate coordination material powder.
[0060] 3) Based on the above weight proportions, linear low-density polyethylene, ethylene-butene copolymer, ethylene-butyl acrylate copolymer, ethylene-methacrylate copolymer, magnesium hydroxide, zinc borate, the zinc tannate coordination material, behenic acid, oleic acid, pentaerythritol diphosphite and tris(2,4-di-tert-butylphenyl)phosphite are added to a high-speed mixer and premixed at 110°C for 3 min.
[0061] 4) The premixed material is fed into a twin-screw extruder for melt blending and extrusion granulation. The melt blending temperature is 155℃ and the screw speed is 450 rpm. Low-smoke halogen-free flame-retardant composite material for insulation layer and low-smoke halogen-free flame-retardant composite material for outer sheath layer are obtained respectively.
[0062] When preparing cables, follow these steps.
[0063] S1: Prepare low-smoke halogen-free flame-retardant composite materials for insulation layers and outer sheaths according to the methods described in 1) to 4) above.
[0064] S2: The low-smoke halogen-free flame-retardant composite material for the insulation layer is added to a mixing mill and mixed at 165°C for 12 minutes. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at 130°C and a screw speed of 275 rpm to obtain the insulation layer material. The low-smoke halogen-free flame-retardant composite material for the outer sheath layer is added to a mixing mill and mixed at 170°C for 25 minutes. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at 190°C and a screw speed of 150 rpm to obtain the outer sheath layer material. In this embodiment, the mixing temperature of the outer sheath layer material is 5°C higher than that of the insulation layer material.
[0065] S3: After surface cleaning and coupling modification treatment of the annealed copper conductor, the insulating material is coated on the outside of the annealed copper conductor using an extrusion device to obtain two insulated wire cores; wherein, the coating temperature of the insulating material is 158℃.
[0066] The surface cleaning and coupling modification treatment includes: S31: First, place the annealed copper conductor in a cleaning solution for surface cleaning. The cleaning solution, based on the total mass of the cleaning solution, includes 85% ethanol, 12% isopropanol, and 3% deionized water. The cleaning temperature is 45°C, and the cleaning time is 1 min.
[0067] S32: The cleaned annealed copper conductor is then placed in an activation solution for surface activation. The activation solution, based on its total mass, includes 1.2% acetic acid and 98.8% deionized water. The activation temperature is 20°C and the activation time is 90 s.
[0068] S33: Subsequently, the activated annealed copper conductor is immersed in a coupling treatment solution, which, based on the total mass of the coupling treatment solution, comprises 0.5% vinyltrimethoxysilane, 65% ethanol, 20% isopropanol, 0.1% acetic acid, and 14.4% deionized water; the immersion time is 90 s; after immersion, it is dried at 130°C for 1 min and cured at 115°C for 600 s to form a coupling modification layer on the surface of the annealed copper conductor.
[0069] S4: Twist the two insulated wire cores at a pitch of 120 mm, and wrap the mica composite tape around their outer periphery to obtain a twisted conductor unit with a flame-retardant insulation layer.
[0070] S5: The outer sheath material is extruded onto the outside of the flame-retardant insulation layer using an extrusion device. The extrusion temperature is 168°C, the extrusion pressure is 25 MPa, and the traction speed is 10 m / min. After extrusion, the material is cooled, shaped, and wound up to obtain the environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable. In this embodiment, the extrusion temperature of the outer sheath material is 10°C higher than the insulation material's covering temperature.
[0071] Comparative Example 1 This comparative example provides an environmentally friendly low-smoke halogen-free flame-retardant twisted-pair cable. The remaining structural components, conductor coupling modification treatment, flame-retardant isolation layer form, cable preparation steps and process parameters are the same as those in Example 1. The difference is that tannic acid metal coordination material is not used in the low-smoke halogen-free flame-retardant composite material, but is replaced by an equal mass of uncoordinated tannic acid powder.
[0072] Specifically, by weight, the low-smoke halogen-free flame-retardant composite material used for the insulation layer and outer sheath includes: 30 parts of high-density polyethylene, 22 parts of linear low-density polyethylene, 18 parts of ethylene-vinyl acetate copolymer, 10 parts of ethylene-octene copolymer, 130 parts of magnesium hydroxide, 3 parts of zinc borate, 12 parts of uncoordinated tannic acid powder, 4 parts of stearic acid, 0.12 parts of pentaerythritol tetrakis[β-3,5-di-tert-butyl-4-hydroxyphenylpropionic acid], and 0.08 parts of dilauryl thiodipropionate.
[0073] In the preparation process of the low-smoke halogen-free flame-retardant composite material, the metal salt coordination and coordination slurry drying treatment in steps 1) and 2) of the preparation method of the low-smoke halogen-free flame-retardant composite material are not performed. Instead, the uncoordinated tannic acid powder is added to the high-speed mixer along with the other components in step 3) for premixing. Then, the cable of Comparative Example 1 is prepared by the same melt blending, granulation, insulation layer coating, double twisting wrapping and outer sheath extrusion process as in Example 1.
[0074] Comparative Example 2 This comparative example provides an environmentally friendly low-smoke halogen-free flame-retardant twisted-pair cable. The composition of the low-smoke halogen-free flame-retardant composite material, the conductor coupling modification treatment method, and the cable preparation steps and process parameters are the same as those in Example 1. The difference is that the flame-retardant isolation layer does not use a wrapped mica composite tape, but is replaced with a regular polyester wrapping tape.
[0075] Specifically, tannic acid iron coordination material and low-smoke halogen-free flame-retardant composite material for insulation layer and outer sheath layer were prepared according to the method of Example 1, and coupling modification treatment of annealed copper conductor surface and insulation layer coating were completed; after twisting, ordinary polyester wrapping tape was wrapped around the outside of twisted conductor unit, and then the cable of Comparative Example 2 was prepared according to the same outer sheath extrusion, cooling and shaping and winding process as in Example 1.
[0076] Performance tests were conducted on the cables prepared in Examples 1-3 and Comparative Examples 1-2. One set of samples was taken from each example. All samples were prepared using annealed copper conductors of the same specifications, the same number of conductor strands, the same nominal insulation thickness, and the same nominal outer sheath thickness, and were continuously processed by the same extrusion and wrapping equipment. Three batches of samples were prepared independently for each set, with each batch of finished cable being 30 m in length. Samples for material performance testing were taken from the granulated materials of the corresponding batches of insulation and outer sheath materials, obtained after hot pressing. Samples for whole-line testing were directly cut from the middle section of the finished cable. All samples were conditioned for 24 hours at 23°C and 50% relative humidity before testing.
[0077] Oxygen index was determined according to GB / T 2406.2-2009. The insulating layer and outer sheath layer were hot-pressed into sheets with a thickness of 3.0 mm, then cut into strips 100 mm long and 10 mm wide. Five parallel samples were taken for each group, and the data from the less favorable side was taken as the result for that group. Peak heat release rate was determined according to GB / T 16172-2007. The corresponding material was hot-pressed into a sheet with a thickness of 3.0 mm, then cut into 100 mm × 100 mm plate-shaped samples. Three parallel samples were taken for each group, and the heat release rate curve was recorded and the peak value was read. Tensile strength was determined according to GB / T 2951.11-2008. The corresponding material was hot-pressed into a sheet with a thickness of 2.0 mm and punched into dumbbell-shaped samples. Five parallel samples were taken for each group, and the average value was taken after testing. The retention rate of elongation at break after heat aging was determined according to GB / T 2951.12-2008. Dumbbell-shaped samples from the same batch were used. The elongation at break before aging was measured first, and then the elongation at break after heat aging was measured. The retention rate was calculated based on the ratio of the elongation at break after aging to that before aging.
[0078] Maximum smoke density was measured according to GB / T 17651.2-2021. A 1.0 m long sample section was cut from the middle of each batch of finished cables, with three parallel samples taken from each group. The change in light transmittance was recorded, and the maximum smoke density value was read. Flame propagation length along the line was measured according to GB / T 18380.12. A 600 mm long single sample section was cut from the middle of each batch of finished cables, with five parallel samples taken from each group. These samples were installed vertically and ignited. After cooling, the maximum distance between the top edge of charring and the ignition reference position was measured. Fire resistance integrity retention time was measured according to GB / T 19216.21-2003. A 1200 mm long sample section was cut from the middle of each batch of finished cables, with three parallel samples taken from each group. A fire resistance test was conducted under energized conditions, and the duration from the start of ignition to line failure or insulation damage was recorded.
[0079] The peel strength between the insulation layer and the conductor was evaluated using a 90° peel test under fixed conditions. A 250 mm long insulated core sample was cut from the middle of each batch of finished cables, with five parallel samples taken from each group. The outer sheath and flame-retardant insulation layer were removed first, and then a 50 mm long section of insulation was pre-stripped from one end of the insulated core to create a free end. During the test, the annealed copper conductor was fixed to the lower clamp, and the free end of the insulation was fixed to the upper clamp. A 90° peel was performed at a speed of 100 mm / min, and the average force during the stable peel phase was recorded and converted to N / cm based on the effective peel width. The same clamp type, clamping length, peel angle, and test speed were used across all sample groups. The test results are shown in Table 1, with all data presented as mean ± standard deviation.
[0080] Table 1 As shown in Table 1, Examples 1-3 exhibited better overall performance compared to Comparative Examples 1 and 2. In Comparative Example 1, replacing the tannic acid metal coordination material with uncoordinated tannic acid powder resulted in a decrease in the oxygen index to 31.7%, an increase in the maximum smoke density to 168, and an increase in the peak heat release rate to 248 kW / m³. 2 The tensile strength, elongation at break retention rate after heat aging, and peel strength between insulation layer and conductor also decreased to 12.1 MPa, 71%, and 13.2 N / cm, respectively. Meanwhile, the flame spread length along the line increased to 268 mm, and the fire resistance integrity retention time was shortened to 67 min. This indicates that uncoordinated tannic acid is difficult to synergistically form a continuous and dense barrier layer with the inorganic flame retardant system during combustion, and has a weak effect on smoke suppression, heat release inhibition, maintaining interfacial bonding stability, and improving the overall structural integrity of the line. Comparative Example 2 retained the low-smoke halogen-free flame-retardant composite material system and the coupling modification layer on the conductor surface, but replaced the mica-coated composite wrapping tape with ordinary polyester wrapping tape. Its oxygen index, maximum smoke density, peak heat release rate, tensile strength, and elongation at break after thermal aging were similar to those of Examples 1-3, indicating that the material's intrinsic properties did not change significantly. However, its flame propagation length increased to 324 mm, and its fire resistance integrity retention time decreased to 41 minutes, indicating that ordinary polyester wrapping tape could not maintain effective radial barrier and structural support under fire conditions, and could not delay heat transfer inward and suppress flame propagation along the twisted-pair structure like the mica-coated composite tape. Therefore, this application, by introducing tannic acid metal coordination materials into the low-smoke halogen-free flame-retardant composite material and setting a mica-coated composite wrapping tape around the outer periphery of the twisted-pair conductor unit, allows the material's inherent flame-retardant and smoke-suppressing capabilities to work in tandem with the overall fire-resistant barrier capabilities of the cable. This simultaneously improves the flame-retardant level, reduces smoke and heat release, and enhances the overall fire resistance integrity and interfacial bonding stability of the cable.
[0081] Although the invention has been described with reference to preferred embodiments, various modifications can be made and technical features can be replaced with equivalents without departing from the scope of the invention. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no conflict of technical concept. The invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. An environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable, characterized in that, It includes twisted pair conductor units, insulation layer, flame-retardant isolation layer and outer sheath layer arranged radially from the inside to the outside; The twisted pair conductor unit consists of two insulated wire cores twisted together, each insulated wire core including a conductor and an insulating layer covering the outside of the conductor; Both the insulation layer and the outer sheath layer are made of low-smoke halogen-free flame-retardant composite material; The flame-retardant isolation layer is disposed on the outer periphery of the twisted pair conductor unit; The pitch of the twisted pair conductor unit is 20 mm to 120 mm; The conductor is an annealed copper conductor, and a coupling modification layer is provided on the outer surface of the annealed copper conductor. The coupling modification layer is a silicon-containing interface layer formed after surface cleaning, acetic acid activation, silane hydrolysis treatment and drying curing.
2. The environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable according to claim 1, characterized in that, The low-smoke halogen-free flame-retardant composite material comprises, by weight: 40 to 65 parts of crystalline polyolefin matrix resin, 10 to 28 parts of ethylene-based flexible toughening copolymer, 90 to 170 parts of metal hydroxide flame retardant, 3 to 15 parts of zinc borate as a smoke suppressant, 2 to 12 parts of tannic acid metal coordination material, 1 to 8 parts of dispersant, and 0.2 to 1.5 parts of antioxidant. The tannic acid metal coordination material is a solid powder material formed by the coordination of tannic acid with iron ions, aluminum ions or zinc ions; the metal hydroxide is aluminum hydroxide and / or magnesium hydroxide.
3. The environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable according to claim 2, characterized in that, The crystalline polyolefin matrix resin is a thermoplastic polyolefin resin having ethylene segments and providing the main crystalline phase, selected from one or more of high-density polyethylene, low-density polyethylene, linear low-density polyethylene, ethylene-butene copolymer or ethylene-hexene copolymer; The ethylene-based flexible toughening copolymer is selected from one or more of ethylene octene copolymer, ethylene vinyl acetate copolymer, ethylene ethyl acrylate copolymer, ethylene butyl acrylate copolymer, or ethylene methacrylate copolymer.
4. The environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable according to claim 2, characterized in that, The antioxidant is a stabilizer used to inhibit thermo-oxidative degradation of the low-smoke halogen-free flame-retardant composite material during melt blending, extrusion molding, and thermal aging. It is selected from one or more of pentaerythritol tetrakis[β-3,5-di-tert-butyl-4-hydroxyphenylpropionate], dilauryl thiodipropionate, trinonylphenyl phosphite, bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl) phosphite, or distearate thiodipropionate.
5. The environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable according to claim 2, characterized in that, The dispersion regulator is selected from one or more of stearic acid, lauric acid, palmitic acid, behenic acid, or oleic acid.
6. The environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable according to claim 2, characterized in that, The preparation method of the low-smoke halogen-free flame-retardant composite material includes the following steps: 1) Tannic acid is added to deionized water to prepare a tannic acid solution with a mass fraction of 2% to 12%, and then a metal salt solution containing iron salt, aluminum salt or zinc salt is added to carry out a coordination reaction. The mass ratio of metal ions to tannic acid in the metal salt solution is (1:3) to (1:12), the reaction temperature is 20℃ to 60℃, and the reaction time is 10 min to 120 min to obtain a tannic acid metal coordination slurry. 2) After solid-liquid separation, washing and drying, the tannic acid metal coordination slurry is used to obtain tannic acid metal coordination material powder, wherein the drying temperature is 50℃~90℃ and the drying time is 2 h~12 h. 3) By weight, the crystalline polyolefin matrix resin, ethylene-based flexible toughening copolymer, metal hydroxide flame retardant, zinc borate, the tannic acid metal coordination material, dispersant and antioxidant are added to a high-speed mixer for premixing. The premixing temperature is 60℃~110℃ and the premixing time is 3 min~15 min. 4) The premixed material is fed into a twin-screw extruder for melt blending and extrusion granulation. The melt blending temperature is 120℃~190℃ and the screw speed is 120 rpm~450 rpm to obtain the low-smoke halogen-free flame-retardant composite material.
7. The environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable according to claim 1, characterized in that, The flame-retardant isolation layer is a wrapped mica-coated composite tape.
8. A method for preparing an environmentally friendly, low-smoke, halogen-free, flame-retardant twisted-pair cable as described in any one of claims 1-7, characterized in that, Includes the following steps: S1: Low-smoke halogen-free flame-retardant composite materials for insulation layers and outer sheath layers are prepared according to the preparation method of the low-smoke halogen-free flame-retardant composite material. S2: The low-smoke halogen-free flame-retardant composite material for the insulation layer is added to a mixer and mixed at a temperature of 120℃~165℃ for 5 min~20 min. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at a temperature of 130℃~185℃ and a screw speed of 150 rpm~400 rpm to obtain the insulation layer material. The low-smoke halogen-free flame-retardant composite material for the outer sheath layer is added to a mixer and mixed at a temperature of 125℃~170℃ for 6 min~25 min. After mixing, it is fed into a twin-screw extruder and melt-extruded and granulated at a temperature of 135℃~190℃ and a screw speed of 150 rpm~420 rpm to obtain the outer sheath layer material. S3: After the annealed copper conductor is surface cleaned and coupled to form a coupled modified layer on its surface, the insulating material is wrapped around the outside of the annealed copper conductor with the coupled modified layer using an extrusion device to obtain two insulated wire cores. S4: Twist the two insulated wire cores at a set pitch and wrap the flame-retardant insulation layer around their outer periphery to obtain a twisted conductor unit with a flame-retardant insulation layer. S5: The outer sheath material is extruded onto the outside of the flame-retardant isolation layer using an extrusion device. The extrusion temperature is 140℃~195℃, the extrusion pressure is 8 MPa~25 MPa, and the traction speed is 10 m / min~80 m / min. After extrusion, the cable is cooled, shaped, and wound up to obtain the environmentally friendly, low-smoke, halogen-free, flame-retardant twisted pair cable.
9. The method for preparing the environmentally friendly low-smoke halogen-free flame-retardant twisted-pair cable according to claim 8, characterized in that, In step S2, the mixing temperature during the preparation of the insulating layer material is 5°C to 20°C lower than the mixing temperature during the preparation of the outer sheath material, and in step S5, the extrusion temperature of the outer sheath material is 5°C to 15°C higher than the covering temperature of the insulating layer material.
10. The preparation method according to claim 8, characterized in that, Step S3, which involves surface cleaning and coupling modification of the conductor, includes: S31: First, place the annealed copper conductor in a cleaning solution for surface cleaning. The cleaning solution, based on the total mass of the cleaning solution, includes 60% to 85% ethanol, 5% to 20% isopropanol and the remainder deionized water. The cleaning temperature is 20°C to 45°C and the cleaning time is 1 min to 8 min. S32: The cleaned annealed copper conductor is then placed in an activation solution for surface activation. The activation solution, based on the total mass of the activation solution, includes 0.2% to 2.5% acetic acid and the remainder deionized water. The activation temperature is 20℃ to 40℃ and the activation time is 10 s to 90 s. S33: Subsequently, the activated annealed copper conductor is immersed in a coupling treatment solution, wherein the coupling treatment solution, based on the total mass of the coupling treatment solution, includes 0.5%–4% silane coupling agent, 50%–80% ethanol, 5%–20% isopropanol, 0.1%–1.2% acetic acid, and the balance deionized water, and the immersion time is 10 s–180 s; after immersion, it is dried at 60℃–130℃ for 1 min–15 min, and cured at 80℃–150℃ for 30 s–10 min to form a coupling modification layer on the surface of the annealed copper conductor.
Citation Information
Patent Citations
Halogen-free low-smoke flame-retardant polyolefin cable
CN121237501A